Consumers’ Attitude towards Usage of Debit and Credit Cards: Evidences from the Digital Economy of Pakistan - Qureshi, Jawaid Ahmed; Baqai, Sana; Qureshi, Muhammad Asif (International Journal of Economics and Financial Issues, 2018)
In the digital economy of Pakistan, banks and financial institutions are continuously engaged in efforts to launch new variants of plastic money. At present, the debit and credit cards are widely accepted, among other forms of plastic money, as convenient mode of payment in Pakistan. This increasing trend of debit/credit card usage is encouraging researchers to analyze the opinions of public regarding plastic card usage. This research undertaking highlights the consumer attitude towards usage of these cards in Karachi by considering demographic factors: income, education, age, and gender along with some attitudinal variables: perception of benefits and risks of plastic money. The data is gleaned through survey from the sample of 372 respondents of Karachi. The results reveal that monthly household income, education, and age do not have any significant impact on the plastic card usage. Moreover, the findings uncover that males are using plastic cards more frequently than females. The inquiry confirmed that debit cards’ usage is more than that of credit cards’ usage. Moreover, the perceived benefits and risks play a significant role in usage of debit and credit cards. Keywords: Consumer Attitude, Debit/Credit Cards, Plastic Card Usage, Marketing of Financial Products JEL Classifications: D12, D53, G2